Effect of the glycaemic index of a pre-exercise meal on metabolism and cycling time trial performance - Moore, L. J. S.; Midgley, A. W.; Thurlow, S.; Thomas, G.; Mc Naughton, L. R. (Journal of Science and Medicine in Sport, 2010)
This study investigated the effects of low or high glycaemic index (GI) foods consumed prior to a 40 km time trial (TT) on metabolism and subsequent endurance performance. Ten male cyclists consumed high GI or low GI meals, providing 1 g kg-1 body mass of carbohydrate, 45 min prior to the TT. The TT performance was significantly (p = 0.009) improved in the low (93 ± 8 min) compared to the high GI trial (96 ± 7 min). Low GI carbohydrate oxidation rate (2.51 ± 1.71 g min-1) was higher (p = 0.003) than the HGI carbohydrate oxidation rate (2.14 ± 1.5 g min-1). Fat oxidation rate was significantly higher (p = 0.002) for the high (0.27 ± 0.17 g min-1) than the low GI trial (0.16 ± 0.14 g min-1). Insulin rose significantly following the high compared to the low GI meal (p = 0.008) but dropped significantly to similar values throughout the TT. No significant differences in either TGA or FFA concentration were observed between the trials. The low GI meal led to an increase in the availability of carbohydrate and a greater carbohydrate oxidation throughout the exercise period, which may have sustained energy production towards the end of exercise and led to the improved TT performance observed.